DEVELOPMENT OF SOCIAL SKILLS SCALE FOR SCHOOL CHILDREN - Jabeen, Ayesha; Mahmood, Zahid; Saleem, Sadia; Subhan, Sara (Journal of Postgraduate Medical Institute, 2022)
Objectives: The present study aimed to develop the socialization skills scale for children aged 7-12 years. Methodology: This cross-sectional study was carried out during the period September 2020 to January 2021 on a sample of 377 government school children in the age range 7-12 years (M=9.60, SD= 1.61) using a multistage sampling technique. The scale was developed using a three step-model of generating item pool, expert validation, and pilot testing. The content validity of the scale was determined by getting the items reviewed by the five clinical psychologists. The social skills scale was administered to children in a one-to-one setting, along with the demographic sheet, Digit span, and mental control (Wechsler memory scale subset) Results: Exploratory factor analysis using Oblimin rotation revealed a two-factor structure of the scale namely expressing emotions and social reasoning with 32% cumulative variance. Confirmatory factor analysis also revealed a two-factor structure with good fit indices (CFI=.90, GFI=.95, TLI=.90). The Cronbach alpha of the scale was found to be .70 and the test-retest reliability was .77. The results of the study are discussed in terms of gender and cultural differences. Conclusion: The study revealed that the 20-item social skills scale is a scale with sound psychometric properties.